Strategic human resource planning for academic libraries : information, technology and organization - Crumpton, Michael A. (Chandos information professional series., 2015)
Strategic Human Resources Planning for Academic Libraries: Information, Technology and Organization provides an in-depth discussion of human resources as a strategic element of a library organization, especially as staffing needs and competencies change. The book focuses on the impact of human resource practices in a library setting, discussing several aspects, including the role of human resources when the library is part of a larger organization, along with information on how to identify strategic objectives that are expected and related to workforce issues. In addition, the book reviews hiring practices, reorganizations of staff, use of temps or time-limited positions, and how students, volunteers, and internships can make a strategic difference overall.